Depression, Estrogens, and Neuroinflammation: A Preclinical Review of Ketamine Treatment for Mood Disorders in Women - Gagne, Collin; Piot, Alexandre; Brake, Wayne G. (Frontiers in Psychiatry, 2022)
Ketamine has been shown to acutely and rapidly ameliorate depression symptoms and suicidality. Given that women suffer from major depression at twice the rate of men, it is important to understand how ketamine works in the female brain. This review explores three themes. First, it examines our current understanding of the etiology of depression in women. Second, it examines preclinical research on ketamine’s antidepressant effects at a neurobiological level as well as how ovarian hormones present a unique challenge in interpreting these findings. Lastly, the neuroinflammatory hypothesis of depression is highlighted to help better understand how ovarian hormones might interact with ketamine in the female brain.